THE ROLE OF THERAPEUTIC CHESS IN EDUCATIONTRAUMAS AND PEDAGOGY - Celal Özbek (Education. Innovation. Diversity, 2023)
In this article as a result of the "Therapeutic Chess" project, which is a new teaching technique designed with an interdisciplinary method on kindergarten-primary school children, the increase in children's interest in chess lesson and expressing themselves in mathematics, music, painting, puzzle solving, board games and philosophical level. It has been observed that the students' ability to learn how to act has increased, and it is aimed to contribute to the socialization, normalization process of children who have experienced trauma, to introduce this technique to more widespread use and to transfer it to teachers.